19 Feasibility of native high-resolution 3D SSFP MR angiography for assessment of the thoracic aorta in pregnant subjects with familial aortopathies. (18th April 2016) - Pickup, L; Moody, WE; Plunkett, E; Thompson, P; Thorne, S; Hudsmith, LE
Abstract : Introduction: Native magnetic resonance angiography (MRA) is recommended to assess the thoracic aorta during pregnancy, avoiding the risks of ionising radiation and contrast agent administration. This guidance is however, based only on consensus opinion supported by limited case reports (level of evidence C). Aim: To evaluate the feasibility of performing native 3D steady-state free-precession (SSFP) MRA in pregnant subjects with inherited aortopathy to guide timing and mode of delivery. Methods: Prospective patients (n = 15) with known thoracic aortic disease underwent native 3D-SSFP MRA at 1.5T (Avanto, Siemens) with high isotropic spatial resolution (1.3×1.3×1.3mm 3 ) using a modified ECG-triggered sequence orientated in a sagittal-oblique plane, aligned along the aortic arch, with a respiratory navigator at the diaphragmatic level (slice thickness 2.00mm; TR/TE: 274/1.5ms). Subjects were imaged during "free breathing" adopting a "left uterine displacement" position, with a wedge under the right buttock, offloading the gravid uterus from the inferior vena cava. Aortic dimensions were measured at 7 levels by two independent blinded observers after an assessment of image quality (score 0–3: 0=poor, 3=excellent). Results: Native 3D-MRA was successfully acquired in all subjects during the mid-trimester (20.6 ± 4.9wk). Subject characteristics and pregnancy outcomes are available in Table 1 . Image quality was deemed excellent in 87% after a mean acquisition time of 3.1 ± 1.5min. Figure 1 provides a typical example of a 3D-MRA image. There was a high level of agreement for aortic measurements, with low intra- and inter-observer variability (ICC ranges; 0.95–0.99 and 0.92–0.96, respectively). All pregnancies reached term (≥37/40) with a mean gestation at delivery of 38.0 ± 0.5wk. Imaging surveillance in combination with satisfactory haemodynamic status permitted vaginal delivery in 60%. Conclusion: Native SSFP MRA provides a robust and safe method to accurately measure the thoracic aorta in pregnant subjects with aortopathy, helping to inform decisions regarding the timing and mode of delivery.